2015
DOI: 10.1055/s-0034-1396330
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Short-Duration Electro-Oculograms with and without Mydriasis in Healthy Subjects

Abstract: Short-duration electro-oculograms allow successful recording, furthermore, the application of mydriasis does not influence the quality of the recording.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A-and b-wave amplitudes of the dark-adapted 3.0 ERG (maximal or standard combined 3.0 cd.s/m 2 rod-cone response) and of the light-adapted 3.0 ERG (single-flash 3.0 cd.s/m 2 cone response) were analysed. EOG recordings were performed on Retiscan equipment (Roland Consult System, GmbH, Brandenburg) [31].…”
Section: Electrophysiologymentioning
confidence: 99%
“…A-and b-wave amplitudes of the dark-adapted 3.0 ERG (maximal or standard combined 3.0 cd.s/m 2 rod-cone response) and of the light-adapted 3.0 ERG (single-flash 3.0 cd.s/m 2 cone response) were analysed. EOG recordings were performed on Retiscan equipment (Roland Consult System, GmbH, Brandenburg) [31].…”
Section: Electrophysiologymentioning
confidence: 99%
“…Fast oscillations were set at 1.5 s, six cycles with a total cycle duration of 75 s. The dark phase of the recording included a pre-adaptation of 6 min followed by alternate fixation with 4-min duration and 20-s pause. The light phase (total duration: 14 min) included 4-min adaptation to light, followed by alternate fixation with 10-min duration and fixation-rest of 20 s. 32 Amplifier was bandpass filtered between 0.1 and 50 Hz. We analyzed the dark-trough amplitude, following the offset of retinal illumination, and the light-peak amplitude, following the re-illumination.…”
Section: Electrooculogrammentioning
confidence: 99%
“…The EOG waveforms were recorded using the Natus EMG/NCV/EP machine (USA). Pupils were not dilated as it was shown that application of pupillary dilatation does not influence the quality or the results of electrooculograms [13]. The bitemporal method was used to record EOG waveforms.…”
Section: Assessment Of Electro-oculographymentioning
confidence: 99%